Physicochemical properties of silicate- and oleate- nanoparticles for heavy metal removal applications - Nora’aini Ali,; Laili Che Rose,; Nur Rafiqah Abdul Razak,; Nurul Syahirah Azman,; Norhafiza Ilyana Yatim,; Nor Azman Kasan, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Utilizing magnetic nanoparticles (MN) to extract heavy metal ions from wastewater is a promising method for metal recovery and can reduce secondary waste production. The objective of this study was to evaluate the changes in physicochemical characteristics of silicate-nanoparticles (MNs-SiO) and oleate-nanoparticles (MNs-C-COOH) prepared via the biocompatible W/O microemulsion technique. The characteristics and properties of MNs-SiO and MNs-C-COOH nanoparticles were investigated by Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR), X-ray Diffraction (XRD), and Vibrating-sample magnetometer (VSM). The performance of this nanoparticles (MNs-SiO), and (MNs-C-COOH) (MNs-SiO), and (MNs-C-COOH) as adsorbents were evaluated for removal of selected heavy metal ions, nickel (Ni2+), manganese (Mn2+) and lead (Pb2+) at different modification agent and pH. It was found that MNs-SiO adsorbent was highly favourable towards Pb2+ (673.4 mg/g) at pH 3, followed by Mn2+ (544.8 mg/g) and Ni2+ (182.43 mg/g) at pH 7, respectively. The MNs-C-COOH adsorbent indicated the high adsorption of Ni2+, which was 254 mg/g at pH 6. For commercial magnetic nanoparticles adsorbent, showed high selection towards Pb2+, 660.13 mg/g at pH 6 and other ions showed less than 5% removal. The performance of modifying agents can be explored as their performance is significantly better than commercial magnetic nanoparticle adsorbents, which can potentially be used in wastewater treatment or recovery of targeted heavy metal ions.